ANALISIS PONDASI BORED PILE DENGAN PRINSIP PROBABILITAS (STUDY KASUS PROYEK HOTEL QUEST SOLO) - Susanto, Agus; Listyawan, Anto Budi; Puspitasari, Dewi (Eco Rekayasa, 2015)
Probabilistic design began more realistic solution compare to the deterministic (conventional) design as it can describe and accommodate of soil variability.  Althought the old approach is widely used, it is confirmed, that almost all natural soils are spatially variable in their properties and rarely homogenous.  This paper focuses on the analysis and design of bored pile foundation on the project of  Solo Quest Hotel based on the probabilistic theory.  The research begins with a certain pre-liminary analysis to prepare the probabilistic analysis of bored pile foundatiaon design, by characterizing the cohesion (cu) from convertion of N value on three SPTs data taken from the site.  It involves an extensive analysis to perform the best-fit distribution of pointwise variability of cohesion (cu) using computer program written in MATLAB.  The next step is deriving the point statistics (i.e. mean, standard deviation, and coefficient of variation) across the site.  Finally, a certain monte carlo analysis using Crystal Ball computer program is carried out to design the bored pile foundation by inputing all data taken from MATLAB analysis.  The bored pile installed in 12 m depth and the diameters of bored pile 0,6 m respectively.  The  bored pile experiences 43.354,455 kN vertical load.  The results show that there is no objection to hypothesis of normality in the Chi-Square analysis.  Compare to the deterministic analysis, the probabilistic design needs more bored pile to resist the vertical load in a safety factor 2,5 and confident limit 95%.  Furtheremore, the higher variation of  cu data the larger number of bored pile is desired.